THE STRUCTURAL AND SEMANTIC DYNAMICS OF WORD FORMATION IN MODERN ENGLISH MORPHOLOGY - Ahtamova Umida (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides an in-depth linguistic investigation into the mechanisms of word formation within the English language. Word formation is a pivotal branch of morphology that dictates how the lexicon adapts to socio-cultural and technological shifts. The study evaluates primary productive processes, such as affixation, compounding, conversion, and various shortening methods including blending and clipping. By analyzing the structural and semantic shifts involved in these processes, the research highlights how English maintains its status as a highly flexible and expansive global tongue.